Tratamento da taquicardia ventricular na cardiopatia chagásica - Andre Assis Lopes do Carmo (2019)
Chagas cardiomyopathy is a chronic fibrosing myocarditis and sustained ventricular tachycardia (VT) is the main cause of sudden death in this population. Implantable cardioverter-defibrillator (ICD) is a well-established therapy for secondary prevention in patients with structural heart disease and catheter ablation approaching epicardial circuits is the main therapy for recurrent or incessant VT. Objectives: a) to assess the efficacy of the ICD for secondary prevention in patients with Chagas cardiomyopathy; b) to examine feasibility and complication rates for ventricular tachycardia ablation performed with laparoscopic guided epicardial access, a technique first described in our Service. Methods: we systematically searched five databases for studies assessing mortality outcomes in patients with Chagas cardiomyopathy and VT treated with ICD implantation or with amiodarone. We examined complication rates of the first eleven cases of VT ablation in patients with Chagas cardiomyopathy using laparoscopic guidance to access epicardial space. Results: six observational studies were included for qualitative and quantitative analysis, totalizing 115 patients in amiodarone group and 483 patients in ICD group. The mortality outcome in ICD population was 9.7 per 100 patient-years of follow-up (95% CI 5.7-13.7) and 9.6 per 100 patient-years in amiodarone group (95% CI 6.7-12.4) (p=0.95). All patients were sent to ventricular tachycardia ablation due to failure of medical therapy and reasons for laparoscopy were megacolon in 10 patient and massive liver enlargement in 1 patient. Epicardial access was achieved in all patients. Complications were 1 severe cardiogenic shock during ablation, requiring mechanical assistance, 1 phrenic nerve paralysis and in one patient, due to a low blood flow at the end of the procedure, for safety reasons, we left a drainage catheter that was removed on the next day. There was no intra-abdominal organ injury and only one death of progressive heart failure, more than one month after procedure, while waiting for heart transplantation. Conclusions: a) the best available evidence derived from small observational studies suggests that ICD therapy in secondary prevention of sudden cardiac death is not associated with a lower rate of all-cause mortality in patients with Chagas cardiomyopathy; b) laparoscopic guided epicardial access in the setting of ventricular tachycardia ablation and enlarged intra-abdominal organ is a simple alternative to more complex surgical access and can be performed with low complication rates.